2014
DOI: 10.1073/pnas.1401864111
|View full text |Cite
|
Sign up to set email alerts
|

The ribosome uses cooperative conformational changes to maximize and regulate the efficiency of translation

Abstract: One of the most challenging unanswered questions regarding the structural biology of biomolecular machines such as the two-subunit ribosome is whether and how these machines coordinate seemingly independent and random conformational fluctuations to maximize and regulate their functional efficiencies. To address this question, we have used ribosome mutagenesis or a ribosome-targeting antibiotic to predictably perturb the dynamics of intersubunit rotation, a structural rearrangement of the ribosome that is essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 29 publications
8
53
0
Order By: Relevance
“…Therefore, coupling between the formation of the half-closed conformation of the L1 stalk and IF2-induced stabilization of the semirotated conformation of the ribosome is likely not mediated by the interaction between the L1 stalk and tRNA bound either in the P/I or E/E state. Consistent with our results, recent smFRET data showed that coupling between intersubunit rotation and L1 stalk movement can occur in vacant ribosomes (36), further supporting the idea that the inward movement of the L1 stalk does not require interaction between the L1 stalk and tRNA.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, coupling between the formation of the half-closed conformation of the L1 stalk and IF2-induced stabilization of the semirotated conformation of the ribosome is likely not mediated by the interaction between the L1 stalk and tRNA bound either in the P/I or E/E state. Consistent with our results, recent smFRET data showed that coupling between intersubunit rotation and L1 stalk movement can occur in vacant ribosomes (36), further supporting the idea that the inward movement of the L1 stalk does not require interaction between the L1 stalk and tRNA.…”
Section: Discussionsupporting
confidence: 92%
“…This series of observation in Chen et al [30] is in good agreement with the results of a fast chemical probing assay [41] and a number of single-molecular fluorescence resonance energy transfer studies [42][43][44], but disagrees with another chemical probing assay [45] and the previous timeresolved cryo-EM study [29]. In comparing the two timeresolved cryo-EM studies, the major reason why the two studies reached different conclusions is the difference in the resolutions of maps (9-12 Å in Chen et al [30] and 23-33 Å in Shaikh et al [29]), which stemmed from the difference in data yield.…”
Section: Time-resolved Cryo-emsupporting
confidence: 82%
“…This suggests that A-site binding of a tRNA liberates the viomycin binding site, which would otherwise be occupied by the monitoring bases. Further evidence that A-site binding of tRNA increases viomycin affinity to the ribosome comes from data presented in a recent single-molecule study (13). From their data we estimate a dissociation constant for viomycin binding to 70S ribosomes with an empty A site as large as 20 μM.…”
Section: Discussionmentioning
confidence: 88%
“…Translocation is catalyzed by elongation factor G (EF-G) in a GTP hydrolysis-dependent manner (7) and occurs via formation of tRNA hybrid states (8), relative rotation of the ribosomal subunits (9), and movement of the L1 stalk (10). Bulk FRET, chemical footprinting, and single-molecule FRET experiments have shown that viomycin stabilizes the ribosome in a pretranslocation state with tRNAs in hybrid A/P and P/E configurations, rotated ribosomal subunits, and the L1 stalk in a closed conformation interacting with the P-site tRNA (11)(12)(13)(14)(15)(16); this structure has been visualized by cryo-EM (17). However, a crystal structure of the viomycin-bound ribosome (18) and one single-molecule FRET study (19) have suggested stabilization of the tRNAs in the classical state.…”
mentioning
confidence: 99%